Post Intensive Care Syndrome in patients affected by COVID-19 - Sara Ciuffi; Beatrice Meucci; Yari Longobucco; Camilla Elena Magi; Carla Amato; Khadija El Aoufy; Paolo Iovino; Alberto Lucchini; Carolinna Forciniti; Pasquale Iozzo; Laura Rasero; Stefano Bambi (Infermieristica Journal, 2024)
Despite improvements in survival rates within the ICU over the years, a substantial number of patients continue to struggle with prolonged return to their initial levels of functionality. The physical, psychological, cognitive, and social alterations that persist beyond hospital discharge due to a critical illness are collectively termed “Post Intensive Care Syndrome” (PICS). This term encompasses patients recovering from critical illnesses and their family members (PICS-F). Considering the potential consequences for COVID-19 patients after discharge from the ICU, this paper aimed to describe the characteristics and frequency of PICS in this specific population. Owing to the recent emergence of COVID-19, evidence is still lacking in scientific literature. Among patients admitted to the ICUs with COVID-19, there is a notably high incidence of alterations in at least one dimension (physical, psychological, cognitive, and social). These observed alterations appear to be comparable to those found in non-COVID-19 patients. However, owing to the limited number of studies in the current literature, this cannot be definitively demonstrated. Similar to non-COVID-19 patients, the implementation of the ABCDEF bundle should be considered for COVID-19 patients to prevent PICS. The published literature underscores the profound impact of COVID-19 on patients admitted to ICUs, resulting in significant alterations in the physical, psychological, and cognitive dimensions of post-intensive care syndrome. However, clinical heterogeneity was present in the reported data, and various assessment scales were employed in different studies for each domain. To address this issue, adoption of standardized assessment tools as part of post-ICU follow-ups at consistent intervals for all patients is recommended.